Adult personality and its relationship with stress level and coping mechanism among final year medical students - Zainah Mohamed,; Muhammad Nur Akmal A,; Nor Syazwani AA,; Sim, TS; Nur Erietika A,; Wan Norshafika WMZ, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2019)
Each human being exhibits their own personality traits and each aspect of stress and coping is essential and related. The relationship between the big five personality traits, coping mechanisms and stress level among final year medical students of Universiti Kebangsaan Malaysia (UKM) was investigated in this study. In this cross-sectional study, 152 final year medical students batch 2017/2018, were randomly selected, excluding those who had chronic diseases, married and repeated final year. The questionnaires used were Big Five Personality Inventory and 12-Item General Health Questionnaire. An open-ended question was used to determine how the respondents cope with their stress. Data was analyzed using SPSS 20.0. Agreeableness was the most common personality trait portrayed among the students, whereas Openness to Experience appeared to be the least. The relationship between the Big Five Personality Traits and coping mechanisms (p=0.016; p<0.05) were significantly related. Students with Neuroticism personality had the highest rate of practicing avoidant coping mechanism, while students with Extraversion personality had the highest rate of practicing active coping mechanism. Total score of stress were significantly difference between the different personality traits (p<0.001; p<0.05). However, the p value of 0.359 (p>0.05) and 0.94 (p>0.05) for the Big Five Personality Traits and level of stress showed no significant results on academic performance. Identified own personality were beneficial for final year medical students as it helps to identify the most effective coping mechanism in reducing stress during studying medicine.